Contrastive hierarchies, privative features, and Portuguese vowels - Carvalho, Joaquim Brandão de (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Dresher’s (2009) Contrastive hierarchy theory (CHT) is intended to provide a unified account of both sides of phonological primes: contrastivity and behaviour. This article explores the point and the possibility of extending CHT, which is based on binary features, to a system of monovalent elements that is much indebted to Schane’s (1984) Particle Phonology. It shows how several aspects of the phonology of European Portuguese nuclei that seem prima facie independent from one another – such as reduction patterns and the inventory of diphthongs and nasal vowels – are constrained by element hierarchy, and, thus, receive a unitary account.